2007
DOI: 10.1007/s11102-007-0038-6
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of a pituitary metastasis from a neuroendocrine tumour: case report and literature review

Abstract: Herein we report a rare case of a pituitary metastasis from a neuroendocrine tumour mimicking an adenoma. Moreover, starting from this unusual case, the relevant literature concerning the diagnosis and management of patients with metastasis at pituitary level is reviewed. A 69-year-old woman was admitted to our Unit for severe headache, diplopia, and critical visual field impairment. MRI showed a large pituitary mass compressing the optic chiasm and infiltrating the cavernous sinus. Trans-sphenoidal biopsy rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…The frequencies of primary sites are summarized in Fig. 1 (10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 100, 101, 10...…”
Section: Resultsmentioning
confidence: 99%
“…The frequencies of primary sites are summarized in Fig. 1 (10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 100, 101, 10...…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, pituitary uptake of 68Ga-DOTATATE or other radiolabeled somatostatin analogues has been demonstrated on PET/ CT (159,160), suggesting that PPRT could be an option for pituitary tumours, as described for neuroendocrine tumours (161,162), including pituitary metastasis (163). Fourteen patients with aggressive pituitary tumours (lactotroph (n = 5), gonadotroph (n = 3), corticotroph (n = 2) somatotroph (n = 3) and mixed somatolactotroph (n = 1)) treated with PPRT are reported in the literature.…”
Section: Peptide Receptor Radionuclide Therapy (Pprt)mentioning
confidence: 97%
“…Similarly, conflicting results using [ 111 In]-DTPA-octreotide in pituitary adenomas were reported [103]. Few case-report studies demonstrated the efficacy and safety of radiolabeled SST-analogs in pituitary metastasis in a patient with NET [104] and in a case of relapsed prolactin-secreting giant pituitary adenoma [105]. …”
Section: Radioactive Somatostatin Analogs For Imaging and Therapymentioning
confidence: 99%